Upaya Peningkatan Literasi melalui Media Majalah Dinding (Mading) Berbasis Kearifan Lokal oleh Mahasiswa Program Studi Pendidikan Kewarganegaraan Universitas Cenderawasih di SDN 02 Abepura - Onnie Lumintang; Martina Kekri (Jurnal Pengabdian Masyarakat Waradin, 2024)
Abstract A maximum of 200 Indonesian words printed in italics with Cambria 10 point. The abstract should be clear, descriptive and should provide a brief overview of community service issues undertaken / researched. Abstracts include reasons for the selection of topics or the importance of research topics / community service, methods of research / devotion and outcome summary. The abstract should end with a comment about the importance of the result or a brief conclusion.